Eosinophilic ascites: A diagnostic and therapeutic challenge - Agrawal, Shefali (World J Gastrointest Surg, 2016)
Eosinophilic gastroenteritis (EGE) is a rare condition characterized by eosinophilic infiltration of the gastrointestinal tract. Depending on the dominant layer of infiltration it is classified into three types namely, mucosal, muscularis and subserosal. The most uncommon variant is the subserosal type characterized by primarily subserosal disease, eosinophilic ascites and peripheral hypereosinophilia. The clinical features are non-specific with history of atopic predisposition and allergy. Endoscopic biopsy is frequently non-diagnostic due to an uninvolved gastrointestinal mucosa rendering its diagnosis a challenge. The mainstay of diagnosis is peripheral hypereosinophilia and eosinophil-rich ascitic fluid on diagnostic paracentesis. Oral steroid therapy is usually the first line of treatment with dramatic response. Due to a propensity for relapse, steroid-sparing therapy should be considered for relapses of EGE. We report a case of subserosal EGE with diagnostic clinical features and treatment response and review the current strategy in the management of eosinophilic ascites.